2018
DOI: 10.3390/nu10060713
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Supplementation Improves Lipid Profiles, Oxidative Stress, and Inflammatory Status in Hyperlipidemic Subjects: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Ferulic acid is the most abundant phenolic compound found in vegetables and cereal grains. In vitro and animal studies have shown ferulic acid has anti-hyperlipidemic, anti-oxidative, and anti-inflammatory effects. The objective of this study is to investigate the effects of ferulic acid supplementation on lipid profiles, oxidative stress, and inflammatory status in hyperlipidemia. The study design is a randomized, double-blind, placebo-controlled trial. Subjects with hyperlipidemia were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(110 citation statements)
references
References 36 publications
4
106
0
Order By: Relevance
“…Recent studies have suggested that C3G potentially exerts functions primarily through C3G metabolites (C3G-Ms) [7], and more than 20 kinds of C3G-Ms have been identified in serum by a pharmacokinetics study in humans [8]. Although the function and mechanism of C3G-Ms are still not clear, protocatechuic acid (PCA) [9][10][11][12], phloroglucinaldehyde (PGA) [1], vanillic acid (VA) [13][14][15], ferulic acid (FA) [16][17][18][19], and their derivates represent the main bioactive metabolites of C3G due to their antioxidant and anti-inflammatory properties. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that C3G potentially exerts functions primarily through C3G metabolites (C3G-Ms) [7], and more than 20 kinds of C3G-Ms have been identified in serum by a pharmacokinetics study in humans [8]. Although the function and mechanism of C3G-Ms are still not clear, protocatechuic acid (PCA) [9][10][11][12], phloroglucinaldehyde (PGA) [1], vanillic acid (VA) [13][14][15], ferulic acid (FA) [16][17][18][19], and their derivates represent the main bioactive metabolites of C3G due to their antioxidant and anti-inflammatory properties. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of researchers have discovered the beneficial influence of FA in stress-induced injury [33]. Treatment with FA has a protective effect by reducing oxidative stress and inhibiting ROS production in PC12 cells treated with the neurotoxin lead acetate [34].…”
Section: Discussionmentioning
confidence: 99%
“…FA through its antioxidant properties is reported to be beneficial in prevention and/or treatment of disorders linked to oxidative stress, including Alzheimer's disease , diabetes , cancers , hypertension, dyslipidemia, and atherosclerosis . In addition, its derivatives have been found effective against several inflammatory diseases due to its anti‐inflammatory properties . There are reports on FA for its potential against diabetes and associated complications.…”
Section: Discussionmentioning
confidence: 99%